Precipitation data from Global Change Experimental Facility (GCEF) since 2014 - Martin Schädler; Paul Remmler (PANGAEA, 2024)
The GCEF (Global Change Experimental Facility) is a large field experiment in Bad Lauchstädt (federal state of Saxony-Anhalt, Central Germany/Germany) for the investigation of the consequences of climate change for ecosystem processes under different land use options. The GCEF consists of 50 plots with a size of 16 m x 24 m. The experiment started in 2014 and is planned to be conducted for at least 15 years. The 50 plots are arranged in 10 blocks (5 plots per block). Half of the blocks are subjected to a climate change treatment. For this, all plots are equipped with a large steel constructions (5 m heigth), mobile shelters and side panels as well as an irrigation system. Each block is equipped with 1 rain sensor (in the grazing plot), thus the values from each block have to be assigned to all the plots within the block. Precipitation data including artificial irrigation in GCEF since 2014. Measurements have been made in the 10 mainplots of the experiment as sum over 15 minutes with tipping scales. The data are sampled to monitor the manipulation of precipitation according to the experimental plan and as basis data of climatic conditions on the plots. For details of the experiment see Schädler et al. (2019), Ecosphere (https://doi.org/10.1002/ecs2.2635) and the document with the detailed experiment design.